Conception of the Transition to Adulthood: Ukrainian Case - Z. Ganeva; V. Pavlenko (University of Sofia, 2014)
Similarly to other European countries, in Ukraine scholars can identify a developmental stage of emerging adulthood. Little work has been done to examine emerging adulthood in Eastern European countries, such as ex-Soviet Union republics like Ukraine, which are making the transition out of communism into the broader free-market economy of Western Europe. Conceptions of the transition to adulthood were examined using data from 117 persons (51 women, 66 men) aged 16-34, including 43 adolescents (aged 16-19), 51 emerging adults (aged 20-29), and 23 young-to-midlife adults (aged 30-35). Participants indicated the characteristics necessary for a person to be considered an adult on a questionnaire containing 43 possible criteria. Results found that the majority of Ukrainian young people did not consider themselves to be adults. The top criteria endorsed emphasised aspects of chronological transitions as criteria for adulthood by a large majority in the study. Among the criteria indicated with least influence are family capacities.